2019
DOI: 10.1088/1742-6596/1340/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook in Blended Learning in Vietnamese Undergraduate Students

Abstract: The study investigated the use of Facebook as an educational tool as well as the influence of Facebook integration into blended learning environment on English pronunciation teaching and learning activities. The subjects for the study consisted of 30 students who were the first-year English majors at Thai Nguyen University of Education. They were divided into two groups: the experimental group and the traditional group. Besides, there was a student teacher from the same university to be the subject of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Facebook retains outstanding features to offer a professional online course for English pronunciation learning, such as live lectures, group discussions, scheduled events and etc. [63]. Besides, English translation concepts teaching in a BL setting enhances the core concept building and mythical concept transformation in translation concepts teaching practices [61].…”
Section: E Effectsmentioning
confidence: 99%
“…Facebook retains outstanding features to offer a professional online course for English pronunciation learning, such as live lectures, group discussions, scheduled events and etc. [63]. Besides, English translation concepts teaching in a BL setting enhances the core concept building and mythical concept transformation in translation concepts teaching practices [61].…”
Section: E Effectsmentioning
confidence: 99%
“…One such application, Elsa Speak Application, specifically designed to assist in pronunciation learning, has been the focus of limited but positive research. Studies by Phuong (2022), Qui et al (2021), Tran (2020), Huong et al (2019), Linh & Thy (2019), and Huong & Long (2018) shed light on the perceptions and effectiveness of ESA in various educational contexts. Phuong (2022) conducted a study at Tay Do University, revealing that students had generally positive perceptions of English learning applications, including Elsa Speak Application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tran's (2020) study on mobile technology for language learning yielded mixed results, but learners using Elsa Speak Application expressed curiosity and a desire to learn. Huong et al (2019) explored the impact of Elsa Speak Application on English pronunciation proficiency, concluding that its use had a positive effect on learning and teaching. Linh & Thy (2019) investigated the flipped classroom model, finding that Elsa Speak Application contributed to improved pronunciation skills and positive attitudes among Vietnamese university students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a similar vein, a partial result of Vu & Bui (2020) [35] was reported that tertiary students' writing competence was improved when Facebook was a component of the blended learning approach. In addition, the result from the study of Huong, Oanh, T., Oanh K., & Luong (2019) [33] presented that Facebook could level up English -major students' pronunciation. (Davis, 1989).…”
Section: Facebook In Elt In Vietnam Contextmentioning
confidence: 99%
“…Nonetheless, there are several studies have been conducted to explore the impact of Facebook on ELT (Tuân & Tư, 2013 [27]; Tran, 2016 [28]; Van & La, 2017 [29]; Nhi & Mai,2018[30]; Le, 2018[31]; Ngo, 2018 [32]; Huong, Oanh.T., Oanh. K., & Luong, 2019 [33]; Loan, 2019 [34]; Thao & Dieu, 2020 [26]; Vu & Bui, 2020 [35]; Nguyen, 2017 [36]). Hence, this study was conducted, and the overall aim of this study expected to open a room so that it would shed light on the attitudes to use of Facebook among English-major students in Vietnam.…”
Section: Introductionmentioning
confidence: 99%